2020
DOI: 10.3126/jnphyssoc.v6i2.34865
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet and Cross-Correlation Analysis of Relativistic Electron Flux with Sunspot Number, Solar Flux, and Solar Wind Parameters

Abstract: The Geostationary Operational Environmental Satellites (GOES) have been monitoring the Earth's radiation environment and is providing the electron flux data (of energy >0.8 MeV, >2 MeV, and >4 MeV) by means of a connected sensor subsystem. Relativistic electron flux is one of the components of the radiation belt which not only affects the electrical system in satellites but also has an impact on Earth’s upper atmospheric climatic variation. We have carried out a study to determine the relation of suns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Cross-correlation is a standard tool for measuring statistical relation among distinctive variables and to measure the degree of similarity and additionally draw identical characters relative to each other in time to explore the unseen new information that can be obtained ; Adhikari Adhikari et al, 2019;Poudel et al, 2020). In this research, we have implemented the cross-correlation method to achieve correlation coefficients and time lag among TEC of eclipse incidence region (Nepal) and non-incidence region (Japan) during the day of the eclipse and quiet day.…”
Section: Cross-correlation Analysismentioning
confidence: 99%
“…Cross-correlation is a standard tool for measuring statistical relation among distinctive variables and to measure the degree of similarity and additionally draw identical characters relative to each other in time to explore the unseen new information that can be obtained ; Adhikari Adhikari et al, 2019;Poudel et al, 2020). In this research, we have implemented the cross-correlation method to achieve correlation coefficients and time lag among TEC of eclipse incidence region (Nepal) and non-incidence region (Japan) during the day of the eclipse and quiet day.…”
Section: Cross-correlation Analysismentioning
confidence: 99%
“…This work extends the cross-correlation to Joule heating, ring current, and auroral precipitation and, as explained above, finds high correlations with relativistic electron population. Poudel et al [34] found a good correlation of relativistic electrons with solar wind velocity and plasma density. The correlation with Joule heating, ring current, and auroral precipitation further supports the inference because the plasma density in the ionosphere is closely related to the magnitude of Joule heating, ring current, and auroral precipitation.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, the variation in all three factors and relativistic electron fluxes are in synchronization. Poudel et al [34] had performed a cross-correlation analysis of relativistic electron flux with sunspot number, solar flux, and solar wind parameters. This work extends the cross-correlation to Joule heating, ring current, and auroral precipitation and, as explained above, finds high correlations with relativistic electron population.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-correlation (C-C) is a method of learning unlike parameters to measure likenesses and plot analogous relative features, which can tell new information (Poudel et al, 2020). It is convenient as a measure of the similarity between two-time series as a function of one's delay relation to the other since its highest happens at the lag at which the two-time series are greatest associated (Menke and Menke, 2012).…”
Section: Methodsmentioning
confidence: 99%